Retinoic acid antagonizes estrogen signaling to maintain adult uterine cell fate - Yan Yin; Meade Haller; Lauren Goldinger; Shivani Bharadwaj; Emily So; Vivian Robles-Pinos; David Chen; Liang Ma (Proceedings of the National Academy of Sciences, 2025)
Classical tissue recombination experiments demonstrate that cell-fate determination along the anterior–posterior axis of the Müllerian duct occurs prior to postnatal day 7 in mice. However, little is known about how these cell types are maintained in adults. In this study, we provide genetic evidence that a balance between antagonistic retinoic acid (RA) and estrogen signaling activity is required to maintain simple columnar cell fate in adult uterine epithelium. Transdifferentiation of simple columnar uterine epithelium into stratified cervicovaginal-like epithelium was observed in three related mouse genetic models, in which RA signaling was perturbed in the postnatal uterus. Single-cell RNA sequencing analysis identified the transformed epithelial cell populations and revealed extensive immune cell infiltration resulting from loss of RA signaling. Surprisingly, disruption of RA signaling led to dysregulated expression of a substantial number of estrogen target genes, suggesting that these two pathways may functionally oppose each other in determining and maintaining uterine epithelial cell fate. Consistent with this model, neonatal exposure to the strong synthetic estrogen, diethylstilbestrol, downregulated expression of a group of RA target genes and led to epithelial stratification and immune cell infiltration in wild-type uterus. Treating RA receptor triple conditional knockout pups with fulvestrant, an estrogen antagonist, reestablished the balance between the two signaling pathways, and effectively prevented the transformation of mutant simple columnar epithelia to metaplastic stratified epithelia. These findings implicate an essential role for RA signaling in maintaining uterine cytodifferentiation by antagonizing estrogen signaling in the postnatal uterus.